La prescripción en el ejercicio de la acción judicial en controversias laborales, estudio de derecho comparado - Fierro Espinosa, Cristian Paul (2024)
Labor Law is such a broad branch that it is necessary to carry on a study of one of the legal institutions that is applied within the exercise of it, this is the case of extinctive prescription and its application in Labor Law, which, over time has been a focus of study due to divided criteria that are related to the intangibility and inalienability of labor rights. In addition to what was mentioned above, this work contributes to society because it seeks the correct functioning of the prescription, in favor of the worker, therefore, the following was questioned: How does the extinctive prescription influence labor disputes?. This research was carried out from a mixed approach, starting from a legal, critical and comparative analysis with Chilean legislation; with the purpose of proposing a reform to art.635 of the Ecuadorian Labor Code, mentioning a reduction in the prescription periods for actions arising from acts or contracts. Among the findings that this work denoted, the idea of reducing the limitation period in favor of the worker stands out, since the simple fact of having an extension of time or an infinite time implies possible violations of workers' rights. It is important to know the criteria of professionals regarding this matter, therefore, a survey was carried out with objective questions to a specific population of lawyers in free practice of the profession, who have knowledge of the matter, with partial results, giving it meaning. to the present work.